Optimizing Micro, Small, and Medium Business Ecosystem Elements to Improve the Economic Competitiveness of North Sumatra - Pasaribu, Ayu Angelina; Butar Butar, Riyani (Journal of Sustainable Economics, 2025)
Micro, small, and medium enterprises (MSMEs) have long been an important pillar in driving economic growth. This study aims to analyze the MSME ecosystem in relation to competitiveness in North Sumatra Province. This research uses the Vector Autoregression Error Correction model. The results show that in the short term, there is an increase in access to capital, which significantly and positively affects income. This is consistent in the long term, where there is a positive and significant effect of increased access to capital in driving the system towards long-term equilibrium. Increased adoption of internet technology has a positive and significant effect. Long-term analysis shows a positive coefficient for internet technology adoption. In the short term, not receiving guidance/training/counseling (BPP) shows a positive and significant effect. However, long-term findings show a negative and significant impact. Short-term findings show that the bank loan variable has a negative and significant impact, which is consistent with long-term findings.